Biofertilizer Business Development Strategy Based on Fermented Water Waste: A Triple Layer Business Model Canvas Approach - Jannah, Wardatul; Ria, Vina Yunita; Ubaidillah, Ubaidillah; Maharani, Anjar; Sihotang, Woulden Hood; Ibanah, Indah; Soetriono, Soetriono; Kuntadi, Ebban Bagus; Damascena, Cindera Rosa (University of Jember, 2024)
Indonesia is a country that has high potential in the agricultural sector. However, the use of fertilizers that are not environmentally friendly, the continuous application of chemicals, and inappropriate land management and cultivation systems will increase land degradation and cause losses for future generations. The